2020
DOI: 10.1111/dth.13202
|View full text |Cite
|
Sign up to set email alerts
|

Topical ketoconazole for the treatment of androgenetic alopecia: A systematic review

Abstract: Androgenetic alopecia (AGA) is common and associated with significant psychosocial distress. Treatment options are needed for patients that do not adequately respond to first line treatments of finasteride or minoxidil. Topical ketoconazole has been proposed as a promising treatment. The goal of this systematic review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…The process of miniaturization is androgen‐mediated in males. In women, female pattern hair loss (FPHL) has emerged as the preferred term for androgenetic alopecia due to the uncertain relationship between androgens and this entity 4‐6 . However, literature supports the effectiveness of finasteride and dutasteride therapy in women with FPHL 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The process of miniaturization is androgen‐mediated in males. In women, female pattern hair loss (FPHL) has emerged as the preferred term for androgenetic alopecia due to the uncertain relationship between androgens and this entity 4‐6 . However, literature supports the effectiveness of finasteride and dutasteride therapy in women with FPHL 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review suggests a randomized controlled trial to evaluate this drug. 26 Moreover, the treatment modality is co-adjuvant therapy. The first choice is hair transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of ketoconazole for the treatment of AGA revealed increased hair shaft diameter and increase in pilary index (percent anagen phase ×diameter) following treatment. Studies also demonstrated clinical improvement of AGA based on photographic evaluation 149 . Shampoos containing 2% ketoconazole may be applied to the scalp as a promising adjuvant or alternative therapy in the treatment of AGA.…”
Section: Supplements and Otc Treatmentsmentioning
confidence: 96%